The Role of Social Communication Websities in Forming the Political Awareness (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research has attempted to identifty of the role communication websites in forming political awareness specially as such websites have invaded human life and become a part and parcel of the different social, political, ecnomical and cultuaral aspect of life in addition to being a significant source of knowledge, a source that rapidly give access to information . Moreover, the research has tackled the most important websites, their positive and negative aspects and the impact of their political awareness. In fact, social communication websites is a vital tool of political change and an effective factor in decision making that results in actual achievements and a main reason behind troubles in the Arab World.  The researcher has reached a conclusion that social communication websites are not a means of communication but also an effective tool in people hands, and rather a political information. Politically speaking, Such websites help in the forming of political awareness, and they are a main factor in the political change that is taking place wide world, irrespective of its positive or negative sides. It is of great importance to stress after all, that such websites have created a massive chaos in the Arab world. Thus, it is essential to be careful while using them.